PENGARUH PEMBERIAN EKSTRAK BIJI PEPAYA (CARICA PAPAYA LINN) TERHADAP KADAR HDL PADA TIKUS PUTIH JANTAN GALUR WISTAR (RATTUS NORVEGICUS) YANG DIINDUKSI DIET TINGGI LEMAK - SUKMA DWI KARTIKA; ILHAM HARIAJI; FANI ADE IRMA; YENITA . (JURNAL ILMIAH KOHESI, 2021)
Cardiovascular disease is the leading cause of death globally, totaling 17.7 million in 2015, representing 31% of all globaldeaths. The death rate of cardiovascular disease that increases every year is Coronary Heart Disease. Modern diets thatcontain lots of cholesterol, accompanied by high food intensity, obesity such as low activity make blood cholesterol levelsdifficult to control so that it can cause dyslipdemia. Experimental Research With Pretest-Posttest Method with control groupdesign. This study used male Wistar rats (Rattus novergicus) induced by a high-fat diet. Where divided into 4 groups, dividedinto negative control, negative control, first treatment (400mg / tail) and second treatment (800mg/tail ). Takes before andafter a diet and a high-fat diet are taken. In this study, the results obtained with the t-test p <0.05, which means that there is arelationship between the provision of papaya seed extract and an increase in HDL levels. In the research results where thedose of 400mg/tail can increase HDL cholesterol levels in the blood. There was a significant relationship between papayaseed extract and the increase in HDL levels in male Wistar rats.